Odontadenia macrantha (Apocynaceae; Apocynoideae): distribution and new records in Mexico - Alvarado-Cárdenas, Leonardo O. (Instituto de Ecología, A.C., 2016)
Background and Objectives: Apocynaceae are one of the most species diverse groups of Mexico with numerous contributions to understand its systematics and distribution. However, some taxa are little known, as in the case of Odontadenia macrantha. A description, new distribution records, and conservation status of O. macrantha in Mexico are presented.Methods: Based on detailed observation of specimens from different herbaria and taxonomic literature, a description of the taxon and a key to morphologically and geographically close species is presented. In addition, an assessment of the conservation status of the species in Mexico, based on the IUCN criteria, and a distribution map are provided.Key results: The presence of this species in Tabasco and Veracruz extends its distribution further northwards. Additionally, these records provided new types of vegetation in which the species grows, such as tropical rain forest, tropical forest with Curatella, tropical deciduous forest and Quercus forest. Odontadenia macrantha is a taxon of variable morphology, which is corroborated here, because it has smaller corollas than the individuals of southern populations. Here is suggested to place this species in the category of Endangered (EN C2ai) for being restricted to a small tropical area with a high anthropogenic activity and few individuals in the observed populations.Conclusions: These new records suggest that the constant review of biological collections to maintain knowledge on taxa updated is needed. In addition, collection activities should be continued in the vegetation remnants of Tabasco and Veracruz.